Open-Label Phase II Prospective, Randomized, Controlled Study of Romyelocel-L Myeloid Progenitor Cells to Reduce Infection During Induction Chemotherapy for Acute Myeloid Leukemia. Issue 29 (10th October 2021) - Desai, Pinkal M.; Brown, Janice; Gill, Saar; Solh, Melham M.; Akard, Luke P.; Hsu, Jack W.; Ustun, Celalettin; Andreadis, Charalambos; Frankfurt, Olga; Foran, James M.; Lister, John; Schiller, Gary J.; et al.
Abstract : PURPOSE: Standard cytotoxic induction chemotherapy for acute myeloid leukemia (AML) results in prolonged neutropenia and risk of infection. Romyelocel-L is a universal, allogeneic myeloid progenitor cell product being studied to reduce infection during induction chemotherapy. PATIENTS AND METHODS: One hundred sixty-three patients with de novo AML (age ≥ 55 years) receiving induction chemotherapy were randomly assigned on day 0 (d0), of whom 120 were evaluable. Subjects received either romyelocel-L infusion on d9 with granulocyte colony-stimulating factor (G-CSF) starting daily d14 (treatment group) or G-CSF daily alone on d14 (control) until absolute neutrophil count recovery to 500/µL. End points included days in febrile episode, microbiologically defined infections, clinically diagnosed infection, and days in hospital. RESULTS: Mean days in febrile episode was shorter in the treatment arm from d15 through d28 (2.36 v 3.90; P = .02). Similarly, a trend toward decreased microbiologically defined infections and clinically diagnosed infection in the treatment arm was observed from d9 to d28 (35.6% v 47.5%; P = .09), reaching a statistically significant difference from d15 to d28 (6.8% v 27.9%; P = .002). Because of this, antibacterial or antifungal use for treatment of an infection was significantly less in the treatment group (d9-d28: 44.1% v 63.9%; P = .01). Significantly fewer patients in the treatment arm received empiric antifungals from d9 tod28 (42.4% v 63.9%; P = .02) and d15-d28 (42.4% v 62.3%; P = .02). Patients in the treatment arm also had 3.2 fewer hospital days compared with control (25.5 v 28.7; P = .001). Remission rates and days to absolute neutrophil count recovery were similar in the two groups. No patients in the romyelocel-L plus G-CSF group died because of infection compared with two patients in the control arm. No graft-versus-host disease was observed. CONCLUSION: Subjects receiving romyelocel-L showed a decreased incidence of infections, antimicrobial use, and hospitalization, suggesting that romyelocel-L may provide a new option to reduce infections in patients with AML undergoing induction therapy.